Hemiptera pest species identified on woody ornamental crops in Galicia northwest Spain - Ares, Jose Luis AndrÃ©s (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
The precise identification of dominant woody ornamental plant species is crucial for the development of sustainable plant protection programs within the Galician region of northwestern Spain. In the present paper, a total number of 49 new different Hemiptera species were identified, 24 Aphidoidea, 2 Phylloxeroidea, 6 Coccidae, 6 Diaspididae, 1 Pseudococcidae, 1 Rhizoecidae, 1 Pentatomidae, 1 Triozidae, 2 Aphrophoridae, 3 Tingidae, 3 Aleyrodidae and 1 Coreidae, in woody ornamental crops of Galicia, as part of author independent consultancy service, carried out from 1999 to 2022. Considering only crop pests, 33 from 49 were new references for woody ornamental crops in Galicia and 23 of them were new references for Spain. With the information obtained by the author, this paper also describes the following new worldwide references: Aphis fabae on Peltaria sp., Myzocallis boernerii on Quercus robur, Tetraneura ulmi on Ulmus minor, Protopulvinaria pyryformis on Gardenia japonica, Saissetia oleae on Cyca revoluta, Rhizoecus falcifer on Phyllostachys aurea, Phyllostachys nigra and Leucothoe fontenesiana, Balanococus diminutus on Viburnum tinus and Nandina domestica, Graphosoma lineatum on Phyllostachys aurea and Phyllostachys nigra, Aphrophora salicina on Grevillea robusta, Grevillea rosmarifolia and Azalea, Corythucha ciliata on Rosa canina, Sambucus nigra as well as on Lavandula angustifolia and Trialeurodes vaporariorum on Ceanothus repens, Metrosideros robusta Polygala myrtifolia and Azalea. A total number of 49 Hemiptera species will be described in the paper.